Novel clinical and molecular findings in Spanish patients with naevoid basal cell carcinoma syndrome. (1st January 2018) - Alonso, N.; Cañueto, J.; Ciria, S.; Bueno, E.; Palacios‐Alvarez, I.; Alegre, M.; Badenas, C.; Barreiro, A.; Pena, L.; Maldonado, C.; Nespeira‐Jato, M.V.; Peña‐Penabad, C.; et al.
Summary: Background: Naevoid basal cell carcinoma syndrome (NBCCS) is an autosomal dominant disorder characterized by developmental alterations and multiple basal cell carcinomas. Mutations in PTCH1, which encodes a membrane receptor for Sonic Hedgehog, are associated with the development of the disease. Most of them produce a truncated protein, which is unable to suppress Smoothened protein and continuously activates the downstream pathway. Objectives: We aimed to characterize 22 unrelated Spanish patients with NBCCS, the largest cohort with Gorlin syndrome reported to date in Spain. Methods: Genomic analysis of PTCH1 was performed in patients with NBCCS and controls, and mutations were analysed using bioinformatics tools. Results: We report for the first time two young patients, one each with uterus didelphys and ganglioneuroma, within the context of NBCCS. One patient showing a severe phenotype of the disease had developed basal cell carcinomas since childhood. Sanger sequencing of PTCH1 in this cohort identified 17 novel truncating mutations (11 frameshift, five nonsense and one mutation affecting an exon–intron splice site) and two novel missense mutations that were predicted to be pathogenic. The patients showed great clinical variability and inconsistent genotype–phenotype correlation, as seen in relatives carrying similar mutations. Conclusions: This study contributes to increase the pool of clinical manifestations of NBCCS, as well as increasing the number of pathogenic mutations identified in PTCH1 predisposing to the condition. The inconsistencies found between phenotype and genotype suggest the involvement of other modifying factors, genetic, epigenetic or environmental.